Psyholoho-pedagogical influence in the management of teaching staff: theoretical aspekts - Burbyga, V. (Problems of Engineer-Pedagogical Education, 2018)
The article is devoted to one of the important areas of educational reform in Ukraine - the creation of conditions for professional teachers and providing them a high status in society. This calls today from the administration of the institution make every effort for the implementation of social and psychological functions of management, which aims to create a favorable social and psychological microclimate necessary for the formation of productive teaching staff, the team of associates who sideby -side solve complex problem - identity formation. In this regard, there is a need to develop new approaches, technologies and mechanisms of educational institutions. The article proved that the most important activities in the head of the institution has such psychological and pedagogical methods of influence as belief requirement, criticism, encouragement and coercion. It is noted that the effectiveness of the methods of rewards and punishments determined by the ability of the head to consider stimulating pedagogical principles: accuracy, fairness, timeliness and transparency. The article states that the choice of method or its reception depends primarily on the conditions in which this method is used, in the managerial situation. Attention is drawn to the fact that the ability to operate with the methods of influence and is formed primarily in the experience of the head of the institution, the personal management practices, but the starting point is the knowledge that all leaders of the range and diversity of methods of psychological and educational impact.